2022
DOI: 10.1088/1674-1056/ac4481
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electrochemical performance in lithium-ion battery via tantalum oxide coated nickel-rich cathode materials

Abstract: Nickel-rich cathode materials are increasingly being applied in commercial lithium-ion batteries to realize higher specific capacity as well as improve energy density. However, low structural stability and rapid capacity decay at high voltage and temperature hinder their rapid large-scale application. Herein, a wet chemical method followed by a post-annealing process is utilized to realize the surface coating of tantalum oxide on LiNi0.88Mn0.03Co0.09O2, and the electrochemical performance is improved. The modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…So far, there is only one study reporting a tantalum oxide coating by wet chemistry with post-annealing step at 550 °C for Ni-rich CAM. 49 However, reported crystallographic data of the coated product and similar results from other studies on Ta-doping 17 suggest at least partial incorporation of tantalum into the host structure of their material. To the best of our knowledge, our study is the first report on pure tantalum oxide coating on CAMs for liquid Li-ion batteries.…”
supporting
confidence: 72%
“…So far, there is only one study reporting a tantalum oxide coating by wet chemistry with post-annealing step at 550 °C for Ni-rich CAM. 49 However, reported crystallographic data of the coated product and similar results from other studies on Ta-doping 17 suggest at least partial incorporation of tantalum into the host structure of their material. To the best of our knowledge, our study is the first report on pure tantalum oxide coating on CAMs for liquid Li-ion batteries.…”
supporting
confidence: 72%
“…It can be seen from Figure 7 that the product Mn 3 O 4 was a solid powder, the baseline of the diffraction peak was flat, the peak pattern was narrow, and the peak intensity was high, so the crystallinity of the product was good. The cell size of Mn 3 O 4 was a = b = 0.576 nm, c = 0.945 nm, and the crystal volume was 0.314 nm 3 . The grain size was around 290 nm according to the Scherrer formula [42], which is consistent with the result of the previous electron microscopy scans.…”
Section: Phase Analysismentioning
confidence: 99%
“…Battery-grade Mn 3 O 4 could be used to prepare cathode materials for lithium-ion batteries and sodium-ion batteries. As one of the main materials for lithium-ion positive electrodes, LiMn 2 O 4 has been mainly prepared through the high-temperature calcination of electrolytic MnO 2 in industry [1][2][3][4]. More and more studies have shown that LiMn 2 O 4 prepared using Mn 3 O 4 has better electrochemical performance compared to electrolytic MnO 2 [5].…”
Section: Introductionmentioning
confidence: 99%
“…With the rise of the new energy vehicle industry, breakthroughs in lithium-ion batteries [1][2][3][4] regarding high energy density and safety performance have become increasingly crucial. Currently, lithium-ion batteries employing organic liquid electrolytes have achieved significant success, and are widely used in commercial applications.…”
Section: Introductionmentioning
confidence: 99%